HAK ORANG KURANG UPAYA MENUNAIKAN SOLAT DI MASJID: ISU DAN CABARAN: The Rights of Persons with Disabilities to Perform Prayers in Mosques: Issues and Challenges - Mahadi, Nurul Izzattie Elnyz; Abdullah, Raihanah; Mat Hussin, Mohd Norhusairi; Mat Salleh, Hasiah; Marlina, (Jurnal Syariah, 2024)
This article explores the rights of persons with disabilities (PWD) in performing prayers in mosques, in line with Islamic principles that emphasize equality and convenience in worship. Mosques, as centers of worship and community, should be inclusive for all, including PWD. However, various issues and challenges hinder their accessibility, such as the lack of PWD-friendly facilities, societal stigma, and limited awareness of PWD rights. This study adopts a qualitative approach by analyzing existing literature, including religious texts, academic studies, and legal frameworks relevant to Malaysia. The article also examines efforts undertaken by mosques and authorities and provides recommendations to improve facilities and societal understanding. This research aims to enhance awareness and drive change toward creating more inclusive mosques for all members of society, including PWD.